2016
DOI: 10.18224/educ.v19i1.5013
|View full text |Cite
|
Sign up to set email alerts
|

Brincadeiras no Parque: sentidos produzidos a partir de vivências na educação infantil

Abstract: Resumo: Considerando as assertivas sobre o brincar na constituição do trabalho educativo na Educação Infantil, neste texto sintetizamos pesquisa, articulada à extensão, buscando compreender os sentidos atribuídos pelas crianças às brincadeiras no parque. Com ancoragem em pressupostos teórico-metodológicos de Bakhtin e Vigostsky, numa abordagem qualitativa exploratória, o estudo envolveu uma turma de crianças de uma instituição de Educação Infantil num município do Espírito Santo, produzindo relatórios das vivê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The topic of "play and early childhood education" has been addressed in several studies carried out in our country (Côco & Soares, 2016;Priolo Filho, Pompermaier, Almeida, & Souza, 2016;Sommerhalder, Nicolielo, & Alves, 2016, among others), but listening to what children have to say about the meaning of playing is still an exception among these investigations. However, as shown by Oliveira, Guimarães and Lima (2013) in a study on the contributions of academic research on the quality of early childhood education in Brazilian institutions, by Cruz and Martins (2017) in research on children's voice and public education policies, and by Marques and Sperb (2013) in a study on the early childhood school from the children's perspective, the interviewed children point out that play is a fundamental component in their educational experience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of "play and early childhood education" has been addressed in several studies carried out in our country (Côco & Soares, 2016;Priolo Filho, Pompermaier, Almeida, & Souza, 2016;Sommerhalder, Nicolielo, & Alves, 2016, among others), but listening to what children have to say about the meaning of playing is still an exception among these investigations. However, as shown by Oliveira, Guimarães and Lima (2013) in a study on the contributions of academic research on the quality of early childhood education in Brazilian institutions, by Cruz and Martins (2017) in research on children's voice and public education policies, and by Marques and Sperb (2013) in a study on the early childhood school from the children's perspective, the interviewed children point out that play is a fundamental component in their educational experience.…”
mentioning
confidence: 99%
“…However, even though: children's right to play is determined by law; theories reiterate the importance of playing for different areas of child development; the most important law on Brazilian education defines the promotion of child global development as a role of early childhood education; the resolution that defines the guidelines for the pedagogical practices in daycare centers and nursery schools elects play as one of the guiding axes for the teacher's work, research has shown that, in general, play is not valued by teachers from most institutions serving children under six years of age in our country (Côco & Soares, 2016;Cruz & Santos, 2016;Jóia, 2018;Portilho & Tosatto, 2014, among others).…”
mentioning
confidence: 99%